Denervation supersensitivity to phenylephrine in guinea-pig vas deferens in vivo and in vitro - Functional studies on alpha(1)-adrenoceptors - Cordellini, S.; Sannomiya, P. (Elsevier B.V., 1999)
The objective was to estimate alterations in adrenergic receptor sites of guinea pig vas deferens, in vivo and in vitro, induced by chronic denervation. The denervation process induced an increased sensitivity (3-fold at the EC50 level) without alteration in the maximum response to phenylephrine in vitro. The sensitivity alteration was characterized by the decrease in the dissociation constant of phenylephrine for alpha-adrenoceptor [K-A: normal tissue 3.50 (0.75-16.21) x 10(-5) and denervated tissue 0.43 (0.11-1.67) x 10(-5) M, p < 0.05] without changing the dissociation constant of prazosin. A decrease in pD(2)' value for phenylephrine-phenoxybenzamine, probably due to a qualitative rather than a quantitative alteration in the alpha-adrenoceptor, was also shown in vitro [pD(2)': normal tissue (8.2776 +/- 0.0402) and denervated tissue (8.0051 +/- 0.0442), p < 0.05]. No change in sensitivity and maximum response to phenylephrine was observed in vivo after denervation, although an increased resistance of vas deferens to phenoxybenzamine blockade has been evidenced in this condition. (C) 1999 Elsevier B.V. All rights reserved.
Keywords: alpha(1)-adrenoceptors; denervation; in vivo and in vitro studies; guinea pig vas deferens; supersensitivity